Analisis Putusan Hakim Terhadap Pertimbangan Alat Bukti dalam Perkara Waris ( Studi Kasus Putusan Nomor 28/Pdt.G/2022/ PN Wates)” - Nadia Towenty Febri Yanti Br. Manihuruk; Galuh Rizki Tarananda; Melissa Oktafina; Teten Tendiyanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the problem where in a trial facts that cannot be taken into consideration by the panel of judges in deciding a civil case in decision Number 28/Pdt.G/2022/ PN Wates. The research was conducted to find out the reasons why the judge did not consider the evidence that had been submitted by the parties. The normative juridical research method with a conceptual approach and case approach was used to analyze the decision Number 28/Pdt.G/2022/ PN Wates as the primary data of the research and secondary data through literature study and for the process of analyzing data based on qualitative descriptive methods. The results showed that the evidence submitted by the litigants in the decision was not considered by the judge because the strength of the evidence was weak. In article 1866 of the Civil Code, evidence that can be submitted to strengthen the arguments in the lawsuit is in the form of written evidence and witness evidence. This study also states that there is a judex factie where the judge examines the facts of the trial, so that the judge can consider it in the decision. Based on this analysis, the judge has responsibility for all evidence submitted by the plaintiff to be considered in making a decision. Evidence is so important in civil trials, because it can affect the judge's confidence in making a consideration to decide a case.